Masculine Trans-formations in Jackie Kay's Trumpet - Koolen, Mandy (Atlantis)

(untitled) (Mount Saint Vincent University, 2010)
Jackie Kay's novel Trumpet shows that transphobic beliefs may negatively affect not only trans-people but also cis-people. Trumpet explores the sex/gender transformations that all people experience and suggests that persecutions of trans-people may work to distract cis-people from their own ultimate inability to fully embody gender ideals.